Implementasi Pengelolaan Berkelanjutan di Desa Wisata Budaya Lingga Kabupaten Karo - Riana Handayani Silalahi; Muhammad Khadry (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
Amidst the rapid development of tourism in Indonesia, cultural village tourism has become increasingly prominent. These villages not only serve as attractive tourist destinations but also as centers for sustainable economic and cultural activities. This study investigates the implementation of sustainable management in Lingga Cultural Tourism Village, Karo Regency, North Sumatra, using the Global Sustainable Tourism Council (GSTC) framework. The village holds significant potential as a cultural tourism destination, especially with its traditional house